Kearifan Lokal dalam Hibriditas Sastra Indonesia Modern - Redyanto Noor (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
Information technology causes cultural transformation that makes global culture is formed. Cultural products called local-genius (local wisdom) are increasingly rare, including art and literature. Classical literature is no longer lived as the orientation of the great values of the past, but is considered a cultural artifact. For modern literature when an author recognizes new conventions and values in his mind, then when he perceives and creates them into literary works, in fact he has made hybrid literature. In biology, hybrid is the result of crossing between one species with another species, naturally or through manipulation. If you look at the origins of language and literature, modern literature is actually hybrid literature, we called modern Indonesian. Really, modern Indonesian author were limited to updating the disclosure method. Basically they remain grounded in the traditions and culture that gave birth to them, which have local-genius (localwisdom).Keywords: Hybrid literature; local wisdom; tradition; culture.IntisariTeknologi informasi menyebabkan terjadi transformasi kebudayaan sehingga terbentuk kebudayaan global. Produk kebudayaan yang disebut local-genius (kearifan lokal) semakin langka, termasuk seni dan sastra. Sastra klasik tidak lagi dihayati sebagai orientasi nilai-nilai masa lampau yang agung, tetapi dianggap sebagai artefak kebudayaan. Bagi sastra modern ketika seorang pengarang mengenal konvensi dan nlai-nilai baru dalam pikirannya, maka ketika ia meresepsi dan mengkreasinya menjadi karya sastra sesungguhnya ia telah membuat sastra hibrida. Dalam ilmu biologi hibrida adalah hasil penyilangan antara satu spesies dengan spesies lain, secara alamiah atau melalui rekayasa. Sebenarnya sastra modern adalah sastra hibrida, hasil penyilangan dari berbagai bahasa dan kebudayaan termasuk sastra Indonesia modern. Meskipun, sebenarnya sastra hibrida tetap mengakar pada budaya etnik penciptanya. Pengarang sastra Indonesia modern sebenarnya hanya sebatas memperbarui cara pengungkapan. Secara esensial mereka tetap berpijak pada tradisi dan budaya yang melahirkannya, yang memiliki local-genius (kearifan local).Kata kunci: Sastra hibrida; kearifan lokal; tradisi; kebudayaan